The participation of young children (under 8) in qualitative research - Brito, Rita (2017)
In the last decades, the role of children in qualitative research has changed, from unknown and incapable subjects, to attentive subjects and active participants. But for your participation to be appropriate and ethical, it is convenient to adopt some methods. Thus, it is intended with this article to make a critical review regarding the participation of children, up to 8 years, in qualitative investigations. Some techniques of data collection used by the authors will be presented in qualitative investigations, with the intention that the children be participative and active subjects. It is also intended to contribute to the methodological discussion and ethical issues in qualitative research with children.